COMMUNITY DYNAMIC OF MICROORGANISM DURING TRADITIONAL COMPOSTING OF DOMESTIC WASTE - VERA EL VIERA (NIM : 30507012); Ketua tim Pembimbing : Prof. Dr. Akhmaloka; Anggota tim pembimb, BAIQ
Composting refers to a classic technology in organic waste treatment, that is a biodegradation process of organic matter into stable material such as humus. During the biodegradation process, almost all of the organic matter degradation occur through the activity of microorganisms. The present of compost microorganism has been studied for decades, however the studies of the present and the role of microorganism in different composting stages were still as an interesting subject to be explored. Information on compost microorganism from tropical country, especially the studies based on molecular biology approach are very limited. Understanding of microbial community and its dynamics are important to control the composting process. This research was focussed to determine the biodiversity and community dynamics of microorganisms, especially bacteria and eukarya, during a traditional composting process of domestic waste. The diversity was analyzed through variation of bacterial 16S rRNA gene fragments (variable region V4-V5 and V3-V5) and eukaryal 18S rRNA gene fragments (variable region V8) of sample from filtration and enrichment in several media, resulted from PCR amplification. The mixture of rRNA gene fragments of amplification products were analyzed by Denaturating Gradient Gel Electrophoresis (DGGE) methods. Several rRNA gene fragments were selected and excised from DGGE bands for further reamplification and sequencing. Measurement of physicochemical parameters such as temperature, pH, water contents and C/N ratio were performed during the composting process. Four phases were recognized in the process as follows: mesophilic, thermophilic, cooling, and maturing phases. Variation of pH during the composting process were detected in the range of 6 Ã‚Â– 9, where the thermophilic phase tends to be alkaline while the other phases tends to be acidic or neutral. Water content decreased from 68.3% at the mesophilic phase to 33.9% at the cooling phase. Measurements of C/N ratio were detected in a range of 24 to 45, with a tendency to be increased in the thermophilic phase and then decreased in the next phases. Seven samples were collected from mesophilic, thermophilic, cooling and maturing phases at temperature 37oC, 49oC, 62oC, 69oC, 72oC, 62oC and 37oC respectively. The DGGE band patterns showed a variation during the composting process from both bacterial and eukaryal samples. The variation were observed in the number of bands, migration positions and density of the DGGE band pattern of each sample. The difference of DGGE patterns were also occured between the mesophilic, thermophilic, cooling and maturing samples. The number of DGGE bands were increased at thermophilic phase for filtration sample of bacteria. Otherwise, the number of DGGE bands were decreased for enrichment sample in several media. These results probably due to the present of dominant bacteria which could be survived in the fluctuated physicochemical environtments, but these dominant bacteria could not be cultured in several media used in this study. The number of DGGE bands were decreased at thermophilic phase for filtration of eukarya sample. These results probably due to the competition of eukarya and bacteria to be survived in the early thermophilic phase. Homological and phylogenetic analysis of selected bacterial DGGE bands showed that Betaproteobacter dominated in the community from all phases. Some fermentative bacteria of Firmicutes group were observed from mesophilic phase and then disappeared in the next phases. The group of Gammaproteobacter was observed only from thermophilic phase, while a number of phylotipe from Betaproteobacter and Gammaproteobacter close related to a member of denitrificans bacteria and Stenotrophomonas and Thermomonas were present. In the cooling and maturing phases, the dominant bacteria were Betaproteobacter of Ralstonia and Burkholderia members. Further analysis of 18S rRNA gene sequence showed that eukarya communities observed in the initial mesophilic phase were dominated by Ascomycota in addition of Stramenopiles and Uncultured Eukaryotes. The diversity of eukarya decreased at thermophilic phase, where dominant bands in mesophilic phase reduced their intensity. The number of DGGE bands increased at cooling and maturing phases and some selected bands were characterized as Ascomycota, Basidiomycota, Zygomycota, Gymnamoeba, and Chlorophyta. The microorganism community changing during the composting process, both for bacteria and eukarya, were successfully observed through the DGGE methods. Information on biodiversity and microorganism community succession from local organic waste composting has not been reported yet. Information on the present of Gammaproteobacter especially Stenotrophomonas and Thermomonas genus was rarely reported in organic waste composting. This information provide a resource for compost culture exploration and its potential in development of composting process effectively besides its potential application as biocontrol agent in agriculture or as bioremediation agent in environment fields.